Impact of Neutrophil-Lymphocyte Ratio in Acral Lentiginous melanoma: Impacto del Índice neutrófilo/linfocito en el Melanoma Lentiginoso Acral | 中性粒细胞与淋巴细胞比率对肢端型恶性黑色素瘤的影响 - Alburqueque-Melgarejo, Joseph (2024)
Introduction: Acral lentiginous melanoma (ALM) is the fourth type of cutaneous melanoma and is the most common subtype in some countries in Latin America and Asia. The neutrophil-lymphocyte ratio (NLR) is an inflammatory marker that has been shown to be useful as a prognostic tool in several malignant neoplasms. Objective: The objective of the study was to evaluate whether NLR has prognostic value in ALM. A retrospective study was conducted that included patients with ALM between 2010 and 2015. Methods: An observational, analytical and retrospective cohort design was used. We worked with a total population of 69 patients with the diagnosis of acral lentiginous melanoma. For the statistical analysis, the SPSS statistical package version 26 was used. Univariate and multivariate Cox proportional regression models were performed. Results: A total of 69 patients with ALM were included. The median age was 68 years, with a predominance of females (55%). Most patients had T4 (34%), lymph node involvement (57.1%), and Clark III (34.4%). In univariate analysis, Clark level III/IV, anaplasia, lymphocytic infiltration, stage III-IV, and NLR were associated with prognoses. In the multivariate analysis, NLR >3.5 (HR 3.9, 95% CI 1.5-10.3, p=0.005) and Clark level III-IV (HR 3.5, 95% CI 1 .6-7.8, p= 0.002) were associated with poor overall survival (OS). Conclusions: NLR is an independent prognostic factor for survival in ALM.